2009
DOI: 10.1098/rsbl.2009.0331
|View full text |Cite
|
Sign up to set email alerts
|

Vocal discrimination of potential mates by female giant pandas (Ailuropoda melanoleuca)

Abstract: In the current study, we used male giant panda (Ailuropoda melanoleuca) bleats in a habituation-discrimination paradigm to determine whether females discriminate between the vocalizations of different males. We found that females habituated to the bleats of a specific male showed a significant dishabituation when they were presented with bleats from a novel male. Further playbacks, in which we standardized the mean fundamental frequency (pitch) and amplitude modulation of male bleats, indicated that amplitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 16 publications
2
33
0
Order By: Relevance
“…Giant panda male and female urine and male anogenital gland secretions contain information that allow individuals to discriminate age, gender and social status [34,[37][38][39][40][41]. We have a basic understanding of chemical signaling in giant pandas [37,38], and recent work on their vocal communications has raised the profile of this aspect of their sociality [23,25]. It is now clear that a great deal of information is coded in the bleats and chirps of giant pandas and ours is the first study to detect a chemical communication response, which was marking, to these auditory signals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Giant panda male and female urine and male anogenital gland secretions contain information that allow individuals to discriminate age, gender and social status [34,[37][38][39][40][41]. We have a basic understanding of chemical signaling in giant pandas [37,38], and recent work on their vocal communications has raised the profile of this aspect of their sociality [23,25]. It is now clear that a great deal of information is coded in the bleats and chirps of giant pandas and ours is the first study to detect a chemical communication response, which was marking, to these auditory signals.…”
Section: Discussionmentioning
confidence: 99%
“…The issue of cross-modalities communication and mate choice is an evolving area of research, and even in highprofile species our understanding of these systems is poor. Recent work on giant pandas (Ailuropoda melanoleuca) [23][24][25][26] has revealed that auditory communication is more complicated than previously believed. Giant pandas are solitary animals that produce 11 different vocalizations across a range of contexts, some of which change in rate and structure during periods of reproductive activity [27,28].…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Recent work has shown that male bleats contain information on the caller's identity and body size (Charlton et al 2009c, b), and that male and female giant pandas attend to this information (Charlton et al 2009a(Charlton et al , 2010b. In addition, the rate of fundamental frequency (F0) modulation in male giant panda bleats is positively correlated to male androgen levels (Charlton et al 2011); raising the possibility that male and female giant pandas could also make use of this information in reproductive contexts.…”
Section: Introductionmentioning
confidence: 96%